DIGITAL LEARNING GOVERNANCE IN PRIMARY SCHOOLS: TPACK-BASED CURRICULUM INTEGRATION AND PRINCIPAL E-LEADERSHIP - Tarekah Hasanah; Agus Pahrudin; Yuberti Yuberti; Achi Rinaldi (El Midad, 2026)
The integration of Information and Communication Technology (ICT) in primary education requires more than providing digital devices; it demands a systematic governance model that connects instructional design, curriculum integration, teacher competence, leadership, and evaluation. This study aims to review and synthesize literature on ICT-based learning governance in primary schools (SD/MI), with specific attention to four review items: learning design and evaluation, TPACK-based curriculum integration, the changing role of teachers, and determinant factors affecting implementation, particularly principal e-leadership and digital learning barriers. This study employed a structured narrative literature review supported by a PRISMA-inspired selection process. The selected literature was analyzed thematically by grouping the findings into governance, actor roles, and determinant factors. The results show that effective ICT-based learning governance in primary schools requires structured instructional design through models such as ADDIE, continuous evaluation through frameworks such as CIPP, and curriculum integration guided by TPACK. The findings also indicate that teachers need to shift from being knowledge transmitters to learning designers and facilitators who can align digital tools with pedagogical strategies and subject content. Furthermore, principal e-leadership emerges as a key determinant in building vision, providing infrastructure, supporting teacher training, and supervising digital learning practices. However, implementation is still challenged by digital divides, limited teacher competence, technical burdens, and pedagogical resistance. This study concludes that the success of digital learning in primary schools depends on integrating TPACK-oriented teacher development, systematic learning governance, and strong principal e-leadership